Case Report: Infantile Urticaria as a Herald of Neonatal Onset Multisystem Inflammatory Disease With a Novel Mutation in NLRP3 - Patrick, Anna E.; Lyons, Eden M.; Ishii, Lisa; Boyd, Alan S.; Choi, Joseph M.; Dewan, Anna K.; Markle, Janet G. (Frontiers in Immunology, 2021)
Neonatal multisystem onset inflammatory disorder (NOMID) is a severe autoinflammatory syndrome that can have an initial presentation as infantile urticaria. Thus, an immediate recognition of the clinical symptoms is essential for obtaining a genetic diagnosis and initiation of early therapies to prevent morbidity and mortality. Herein, we describe a neonate presenting with urticaria and systemic inflammation within hours after birth who developed arthropathy and neurologic findings. Pathologic evaluation of the skin revealed an infiltration of lymphocytes, eosinophils, and scattered neutrophils. Genetic analysis identified a novel heterozygous germline variant of unknown significance in the NLRP3 gene, causing the missense mutation M408T. Variants of unknown significance are common in genetic sequencing studies and are diagnostically challenging. Functional studies of the M408T variant demonstrated enhanced formation and activity of the NLRP3 inflammasome, with increased cleavage of the inflammatory cytokine IL-1β. Upon initiation of IL-1 pathway blockade, the infant had a robust response and improvement in clinical and laboratory findings. Our experimental data support that this novel variant in NLRP3 is causal for this infant’s diagnosis of NOMID. Rapid assessment of infantile urticaria with biopsy and genetic diagnosis led to early recognition and targeted anti-cytokine therapy. This observation expands the NOMID-causing variants in NLRP3 and underscores the role of genetic sequencing in rapidly identifying and treating autoinflammatory disease in infants. In addition, these findings highlight the importance of establishing the functional impact of variants of unknown significance, and the impact this knowledge may have on therapeutic decision making.